2015
DOI: 10.1111/ppe.12251
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Risk Factors for Fetal Growth Restriction Increase the Probability of Antenatal Detection? A French National Study

Abstract: Our results suggest that better risk assessment could improve antenatal identification of FGR. Sex-specific fetal growth references should be used to avoid systematic bias linked to sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
(99 reference statements)
0
25
0
2
Order By: Relevance
“…First, because almost all women have a third‐trimester scan in France, there may be less of a socioeconomic gradient associated with detection. Previous French studies of antenatal detection of FGR and of congenital heart defects have shown that sociodemographic factors are not related to detection. While cases were more likely to be immigrants and less likely to be employed than were controls, the proportions which received a third‐trimester scan were similar and nearly 80% of stillbirths which did not have FGR detected occurred in women who had undergone all three recommended routine scans.…”
Section: Discussionmentioning
confidence: 99%
“…First, because almost all women have a third‐trimester scan in France, there may be less of a socioeconomic gradient associated with detection. Previous French studies of antenatal detection of FGR and of congenital heart defects have shown that sociodemographic factors are not related to detection. While cases were more likely to be immigrants and less likely to be employed than were controls, the proportions which received a third‐trimester scan were similar and nearly 80% of stillbirths which did not have FGR detected occurred in women who had undergone all three recommended routine scans.…”
Section: Discussionmentioning
confidence: 99%
“…[11] A recent French study (N=14 100) highlighted difficulties with the detection of fetal growth restriction even in the presence of obstetric and medical risk factors for the condition, and suggested that better risk assessment could improve antenatal identification. [12] In SA ~50% of stillbirths occur in a seemingly healthy mother who does not present with any clinical complications antenatally. [13] Maternal complications are also not increased in SGA stillbirths RESEARCH compared with AGA and large-for-gestational-age (LGA) stillbirths.…”
Section: Researchmentioning
confidence: 99%
“…In highincome countries, it is estimated that up to 76% of SGA cases can be detected during the antenatal period; [25] however, other studies have reported on difficulties of detecting IUGR. [12] Limited resources in LMICs mean that palpation and fundal height are commonly used methods to predict growth restriction, despite little evidence to support their effectiveness. [10] The detection of fetuses at risk of stillbirth is further complicated by the fact that ~50% occur in a seemingly healthy mother, with no increase in the proportion of unhealthy mothers in SGA pregnancies.…”
Section: Researchmentioning
confidence: 99%
“…Vale ressaltar que não consta das diretrizes do pré-natal no Brasil 19 o monitoramento via ultrassonografia para o crescimento intrauterino, conforme recomendado em outros países, como França e Canadá 32,33 . O acréscimo desse procedimento pode ampliar a detecção do CIR e tornar mais eficaz o pré-natal no controle desse desfecho.…”
Section: Considerações éTicasunclassified